INNOVATIVE DEVELOPMENT OF BUSINESS STRUCTURES IN THE DIGITAL ECONOMY - Кириленко, Сергій В. (Journal of Strategic Economic Research, 2025)
The presented work substantiates that the innovative development of business structures is a key factor in their successful functioning in the conditions of the modern digital economy, characterized by rapid technological changes, globalization and a high level of competition. Digitalization, as an integral part of these processes, transforms traditional business models, allowing companies to interact with customers more effectively, optimize operational processes and expand opportunities for innovation. It is emphasized that modern business is faced with the need to integrate the latest technologies, such as artificial intelligence, big data, blockchain and the Internet of Things, to ensure sustainability and competitiveness in the market. At the same time, innovative development in the conditions of the digital economy requires companies to be flexible, adaptable and quick to respond to changes in the environment. In particular, this applies to the introduction of new forms of work organization, interaction with customers and partners, as well as the creation of new products and services that meet the requirements of digital reality. The purpose of the presented work is to consider the features of modern innovative development of business structures in the digital economy. The main research methods: analysis, synthesis, deduction, induction, logical, generalization, comparison, comparison, graphic and tabular. Thus, innovative development of business structures in the digital economy is an important component of the strategic success of enterprises in the modern competitive environment. Digitalization allows companies not only to optimize existing processes, but also to create new products, services and business models that meet the requirements of a rapidly changing market. The introduction of innovative technologies, such as artificial intelligence, big data, blockchain and the Internet of Things, helps to increase the efficiency of management decisions, improve interaction with customers and partners and provides companies with competitive advantages. However, to achieve sustainable development in the digital economy, business structures must be ready for constant changes and adaptations, which requires flexibility, investment in the latest technologies and continuous learning. Therefore, the successful implementation of innovative development requires not only technical knowledge, but also strategic thinking, risk-taking and the ability to quickly respond to new challenges. In the long term, the adaptation of business structures to digital transformation will not only increase their competitiveness, but also contribute to overall economic development, the creation of new jobs and improving the quality of services at the global level.